EMPHYSEMATOUS CYSTITIS - CASE REPORT AND IMAGING FEATURES - BASHEER AHAMED, (International Journal of Pharma and Bio Sciences, 2015)
Emphysematous cystitis is a rare bacterial infection of the bladder, which results in the presence of gas in the bladder wall, laymen, and surrounding tissues. The most important factors involved in this disease are diabetes mellitus, dysuria and neurogenic bladder, with predominance of female gender.We present a case of a 64 years old female patient, with diabetes mellitus tip 2, who presented in our emergency department with fever, abdominal complaint, olyguria for the last one month. Abdominal CT (computer tomography) revealed gas in the bladder with thickening of bladder wall and formation of an air-ï¬‚uid level. Laboratory test showed anemia and leukocytosis. Urine culture showed elevated growth of Escherichia coli (E. coli). The diagnosis was emphysematous cystitis and patient started the antibiotic specific therapy.